Structure of the dual-function fructose-1,6/sedoheptulose-1,7-bisphosphatase from Thermosynechococcus elongatus bound with sedoheptulose-7-phosphate - Cotton,CAR; Kabasakal,BV; Miah,N; Murray,JW (Acta Crystallographica Section F, 2015)
The dual-function fructose-1,6/sedoheptulose-1,7-bisphosphatase (FBP/SBPase) in cyanobacteria carries out two activities in the Calvin cycle. Structures of this enzyme from the cyanobacterium Synechocystis sp. PCC 6803 exist, but only with adenosine monophosphate (AMP) or fructose-1,6-bisphosphate and AMP bound. The mechanisms which control both selectivity between the two sugars and the structural mechanisms for redox control are still unresolved. Here, the structure of the dual-function FBP/SBPase from the thermophilic cyanobacterium Thermosynechococcus elongatus is presented with sedoheptulose-7-phosphate bound and in the absence of AMP. The structure is globally very similar to the Synechocystis sp. PCC 6803 enzyme, but highlights features of selectivity at the active site and loop ordering at the AMP-binding site. Understanding the selectivity and control of this enzyme is critical for understanding the Calvin cycle in cyanobacteria and for possible biotechnological application in plants.